Study of Physical Characteristic and Equivalence between Generic and Branded Name of Phenylbutazone Tablet - Akib, Nur Illiyyin; Husnaeni, Husnaeni; Zubaydah, Wa Ode Sitti; Mallarangeng, Andi Nafisah Tendri Adjeng (Pharmauho: Jurnal Farmasi, Sains, dan Kesehatan, 2017)
Physical characterization and equivalence testing of generic and branded names of phenylbutazone tablets have been done. The information about quality of generic drugs is expected to increase the use of generic drugs by health practitioners and public. Dissolution test carried out by in vitro had correlation with bioequivalence by in vivo test. Sample of dissolution testing were generic (G) and branded (A and B) names of 200 mg phenylbutazone tablets. Physical characteristic test performed by uniformity weight test, hardness and disintegration time. Dissolution test were conducted by using basket and spectrophotometry ultra violet method in 200-400 nm wavelength. The result of uniformity weight of generic drug and branded drug was 352,02 mg and 352,82 mg, the hardness of generic was 9,58 kgf and branded was 9,50 kgf, and disintegration test result of generic was 16,1 minutes and branded was 3 minutes. The result of dissolution testing were dissolution profile and dissolved concentration at 30 minutes that compared to qualify of USP XXXII. Relative bioavailability testing of generic to A brand was 101.580 and generic to B brand was 105.275. Based on statistical test, there was no significant different or pharmaceutical equivalent. The generic tablets were equivalent to A and B branded names tablets with similar factors 82.120 and 74.271.Keywords: Equivalence, Dissolution, Salbutamol tablet; generic name, branded name